Perilaku Konsumen dalam Berinvestasi Emas Digital Melalui Platform Tokopedia - Titis Indrawati; Aji Damanuri; Shinta Maharani (Journal of Economics, Law, and Humanities, 2023)
Tokopedia is an e-commerce that has a gold investment feature, namely Tokopedia Gold,which collaborates with Pegadaian. Tokopedia is the most popular e-commerce in Indonesiawith the number of monthly web visitors reaching 147.8 million in the second quarter of 2021beating other e-commerce. Tokopedia Gold Pegadaian uses a cash & wadi'ah sale andpurchase contract. Since the Tokopedia Emas feature was launched in 2018, the trend ofbuying gold transactions at Tokopedia has increased by almost 30 times, even though thespread of Tokopedia Gold, which works with Pegadaian, is 4.5% higher than direct goldinvestment at Pegadaian Digital, which is around 3%. It is necessary to know what are thefactors that influence consumer behavior in deciding to choose digital gold at Tokopedia. Thisresearch is a qualitativeresearch. Data collection techniques through interviews, observation,and documentation. Analysis with the theory of consumer behavior. The purpose of this studyis to analyze the mechanism of digital gold investment, to analyze the factors that influenceconsumer behavior in investing in digital gold, and to analyze the impact of digital goldinvestment in Tokopedia on consumer behavior. The results of the study show that the digitalgold investment mechanism influences consumer behavior because it is quite easy andpractical from the choice of product, brand, dealer, time of purchase, purchase amount, andpayment method. Factors that influence consumer behavior, namely consumer psychologicalfactors, are the most influential in investing in digital gold at Tokopedia. Then culturalfactors have a fairly good influence, but social and personal factors have little influence. Aswell as investing in gold has both positive and negative impacts, the many conveniencesoffered, especially attractive promos, make consumers satisfied making purchases, therebyinfluencing consumer behavior to invest in digital gold on Tokopedia continuously.